Relative Source Power: A novel method for localizing epileptiform EEG discharges. (January 2022) - Scherg, Michael; Schulz, Reinhard; Berg, Patrick; Cho, Jae-Hyun; Bornfleth, Harald; Kural, Mustafa A.; Woermann, Friedrich G.; Bien, Christian G.; Beniczky, Sándor
Highlights: Interictal discharges (IEDs) were found in 33 of 41 patients (80%) with extratemporal lesions when reviewing EEG in source space. A source region with 20 mm radius contained lesioned tissue in all 33 cases when using CLARA or relative source power imaging. In the 21 operated patients sensitivity was 82% and specificity 50%. Abstract: Objective: To validate relative source power (RSP) imaging of extratemporal interictal epileptiform discharges (IEDs). Methods: The accuracy of RSP was validated in a cohort of patients with extratemporal focal epilepsy and a confined epileptogenic lesion (<19 cm 3 ) using distance to the lesion, concordance with resected area and postoperative outcome. Performance was compared with three conventional methods: voltage maps, equivalent current dipole and a distributed source model. Results: Thirty-three of 41 consecutive patients (80%) had IED averages suitable for analysis. While the peak negativity in voltage maps localized above the epileptogenic lesion only in 18 cases, RSP-maps matched in 29 cases (88%, p < 0.0026). Source localization showed a median distance of 9.8 mm from the lesion. Source-regions with 20 mm radius included 98% of all source-to-lesion distances. In the 21 surgical cases, outcome showed a sensitivity of 82.35% and specificity of 50% without significant differences between the three source imaging methods. Conclusions: RSP-maps provide a rapid, intuitive and more accurate source estimation than voltage maps. At sublobar level, RSP localizes with an accuracy similar to conventional methods and results of previous studies. Significance: The definition of a source region with 20 mm radius helps in guiding further exploration in extratemporal focal epilepsy.